Preparation of fortified bread by incorporating blends of Helianthus annuus and Myristica fragrans flours: Assessment of functional, physicochemical, and organoleptic properties. Issue 12 (14th October 2022) - Aziz, Mahwash; Ramzan, Rabia; Muhammad, Zafarullah; Khalid, Nazia; Batool, Rizwana
Abstract: Bread is a fundamental food in many countries and comes in various forms. Bread fortified with functional ingredients attracted growing research in recent years. In the present investigation, fortification of whole wheat flour with nutmeg powder was carried out at different levels WSN1 (4% nutmeg), WSN2 (10% sunflower + 4% nutmeg), WSN3 (20% sunflower+4% nutmeg), and WSN4 (30% sunflower + 4% nutmeg). The functional attributes of flour blends were investigated. Furthermore, fortified bread during eight days of storage was determined for compositional analysis and total caloric value. The functional characteristics, that is, water and oil holding capacity (1.88–2.16 and 2.32–4.10, respectively), emulsion activity (40.13–57.58), and stability (38.04–49.83), swelling (15.02–17.25) and foaming stability (13.96–21.39) improved highly significantly by fortification. The minerals content was observed in WSN4 > WSN3 > WSN2 > WSN1 > WSN0 order. The maximum DPPH was observed in WSN4 as 44.28 ± 0.03%. From the current results, based on organoleptic properties, the incorporation of sunflower at about 20% with 4% nutmeg is better and acceptable (7.49 ± 0.01) for the commercialization of products in the industrial sector. Novelty impact statement: The findings of this study are important from the nutritional point of view as bread fortification with natural sources will help to reduce nutritional deficiencies. Incorporating sunflower seeds and nutmeg flour blends in whole wheat flour to prepare fortified bread enhanced bread's nutritional value and improved bread quality characteristics. Utilizing the flour blends could be a promising approach to making fortified bread having a balanced amino acid profile to meet the Lysine deficiency in whole wheat flour.